2002
DOI: 10.1128/mcb.22.15.5585-5592.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Paternally Expressed Pref-1/Dlk1 Display Growth Retardation and Accelerated Adiposity

Abstract: Preadipocyte factor 1 (Pref-1/Dlk1) inhibits in vitro adipocyte differentiation and has been recently reported to be a paternally expressed imprinted gene at human chromosome 14q32. Studies on human chromosome 14 deletions and maternal uniparental disomy (mUPD) 14 suggest that misexpression of a yet-to-be-identified imprinted gene or genes present on chromosome 14 causes congenital disorders. We generated Pref-1 knockout mice to assess the role of Pref-1 in growth and in vivo adipogenesis and to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
364
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(400 citation statements)
references
References 33 publications
28
364
3
5
Order By: Relevance
“…Forced expression of dlk in 3T3-L1 cells was reported to inhibit adipogenesis, whereas suppression of dlk promoted the process and accordingly, dlk was suggested to play an important role in the maintenance of the preadipose state. In support of this hypothesis, recent studies on dlk1-null mice demonstrated that lack of dlk expression was associated with obesity 47 while transgenic mice expressing the full ectodomain of dlk (dimeric form) exhibited inhibition of adipogenesis and impairment of adipocyte function leading to development of metabolic abnormalities. 48 Apart from its func- tion in adipocyte differentiation, dlk has been shown to participate in cell-to-cell interactions occurring in the hematopoietic environment of the bone marrow through regulation of stromal cell signals involved in both selfrenewal and differentiation of hematopoietic stem cells into highly proliferative myeloid-erythroid precursors.…”
Section: Discussionmentioning
confidence: 68%
“…Forced expression of dlk in 3T3-L1 cells was reported to inhibit adipogenesis, whereas suppression of dlk promoted the process and accordingly, dlk was suggested to play an important role in the maintenance of the preadipose state. In support of this hypothesis, recent studies on dlk1-null mice demonstrated that lack of dlk expression was associated with obesity 47 while transgenic mice expressing the full ectodomain of dlk (dimeric form) exhibited inhibition of adipogenesis and impairment of adipocyte function leading to development of metabolic abnormalities. 48 Apart from its func- tion in adipocyte differentiation, dlk has been shown to participate in cell-to-cell interactions occurring in the hematopoietic environment of the bone marrow through regulation of stromal cell signals involved in both selfrenewal and differentiation of hematopoietic stem cells into highly proliferative myeloid-erythroid precursors.…”
Section: Discussionmentioning
confidence: 68%
“…One of such factor could be the suppression of GH expression by overexpressed Dlk1. Interestingly, Dlk1 knockout animals are also smaller that the wild-type littermates [43]. This paradox could be explained in part by the ability of Dlk1 to control differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…DLK1 protein, also known as pref-1, SCP-1, Zog, FA1, and pG2 (Lee et al, 1995;Laborda, 2000), is expressed in a variety of murine and human fetal cells, but it is present only in a limited number of adult tissues (Cooper et al, 1990;Jensen et al, 1993;Laborda et al, 1993;Tornehave et al, 1996;Floridon et al, 2000). DLK1 participates in several differentiation processes including adipogenesis (Smas and Sul, 1993;Boney et al, 1996;Garces et al, 1999), hematopoiesis (Moore et al, 1997;Bauer et al, 1998;Kaneta et al, 2000), and adrenal gland development (Cooper et al, 1990;Gaetano et al, 1992), as well as wound healing (Samulewicz et al, 2002); it is also involved in the control of embryonic growth (Schmidt et al, 2000;Takada et al, 2000;Moon et al, 2002). A recent report suggests that DLK1 acts as a negative regulator of Notch1 (Baladron et al, 2005).…”
mentioning
confidence: 99%